Infantry combat. Part three: beachhead at Salerno. Part four: operations on Guadalcanal.
This pamphlet is the second of a series devoted to factual narratives from theaters of operations. Part I of the Infantry Combat series dealt with the operations of a rifle company at Eddekhila, North Africa, while part II was the story of a rifle platoon leader who took part in the capture of Attu. Both narratives were arranged in chronological order and gave fairly complete pictures of small-unit operations during specific periods of combat. Part III describes a phase of the Salerno operations from a different standpoint. The narrative is based upon the report of a field officer who participated in the operation and who supplemented his personal observations with extracts from unit journals and by interviews with officers and men who took part in the action. The narrative, consequently, gives only a general account of one division's operations over a period of nine days, plus what may be termed "action flashes" concerning a number of units and individuals. Part IV contains a talk given by Major General Robert L. Spragins (Chief of Staff of troops on Guadalcanal, Tulagi, and Florida Islands during the operations) to selected elements of the Hawaiian Department, the 24th / 27th / 8th Infantry Divisions, and the 89th and 71st Light Divisions.